Engaging with nature and work: associations among the outdoor environment and employee outcomes - Brossoit, Rebecca M., author; Crain, Tori L., advisor; Fisher, Gwenith G., committee member; Ganster, Daniel C., committee member; Rickard, Kathryn M., committee member; Eakman, Aaron M., committee member (Colorado State University. Libraries, 2021)
There is substantial evidence that contact with nature is related to positive health and well-being outcomes, but extensions of this research to work-related outcomes is sparse. Some organizations are redesigning workspaces to incorporate nature and adopting nature-related policies, warranting a need for empirical studies that test the influence of nature on employee outcomes. The present mixed-methods study tests and extends the biophilic work design model (Klotz & Bolino, 2020) to examine how the type of outdoor environment (i.e., urbanity and natural amenities) and experiences of time spent outside (i.e., amount of time outside, enjoyment of time outside, outdoor activities), influence employee engagement and creativity. Participants included Amazon's Mechanical Turk workers and working students (N = 803). There were significant indirect effects of natural amenities where employees work on emotional engagement through spending more time outside at work. Similarly, there were indirect effects of natural amenities where employees live on emotional engagement and creativity, through spending more time outside during nonwork time. Additionally, there were indirect effects of natural amenities where employees live on emotional engagement, cognitive engagement, physical engagement, and creativity, through greater enjoyment of nonwork time spent outside. Different types of outdoor activities were identified in the qualitative analyses, which were correlated with the type of outdoor environment where employees work and live, the amount and enjoyment of time spent outside, as well as work-related outcomes. This study has implications ranging from employee time use and organizational effectiveness to policy change and urban planning.